In the Line of Fire: A Memoir - Musharraf, Pervez (Rawalpindi Services Book Club, 2006)
According to Time magazine, Pakistan's President Pervez Musharraf holds "the world's most dangerous job." He has twice come within inches of assassination. His forces have caught more than 670 members of al Qaeda in the mountains and cities, yet many others remain at large and active, including Osama bin Laden and Ayman Al Zawahiri.
Keywords: In The Line Of Fire: A Memoir -- History -- Politics and government -- Presidents